2014
DOI: 10.5944/rppc.vol.19.num.1.2014.12981
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality exposure for OCD: Is it feasible? [Exposición mediante realidad virtual para el TOC: ¿Es factible?]

Abstract: Abstract:During the past decade, the implementation of 3D visualization and Geographic Information System (GIS) in archaeological research has increased and is now well established. However, the combination of these two factors remains rather complicated when faced with archaeological data. Some of the characteristics of this discipline impose the development of applications that will be able to cope with all of the specificities of archaeological data. Our research aims to create an Archaeological Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Previous studies revealed that VR tasks are effective in triggering anxiety in individuals with contamination obsessions (Belloch et al, 2014;Laforest, Bouchard, Cretu et al, 2016). This study extends previous research by showing that VR can be used as a disgust-provoking tool in addition to anxiety.…”
Section: Mediation Analysissupporting
confidence: 85%
See 4 more Smart Citations
“…Previous studies revealed that VR tasks are effective in triggering anxiety in individuals with contamination obsessions (Belloch et al, 2014;Laforest, Bouchard, Cretu et al, 2016). This study extends previous research by showing that VR can be used as a disgust-provoking tool in addition to anxiety.…”
Section: Mediation Analysissupporting
confidence: 85%
“…Consistent with studies demonstrating the effects of anxiety on handwashing behavior (Cougle et al, 2007), the increase in anxiety and disgust levels in the HCF group could have led to a greater urge to wash hands. These findings provided further support for prior research that suggests the use of VR to induce various OCD symptoms and urge to neutralize (Belloch et al, 2014;Kim et al, 2008;Laforest, Bouchard, Cretu et al, 2016;van Bennekom et al, 2017).…”
Section: Mediation Analysissupporting
confidence: 80%
See 3 more Smart Citations